(untitled) (Journal of Comparative Social Work, 2022)
Background: Although some individuals in Germany’s and Austria’s Bavaria–Tyrol border region live in one country but work, study, shop and/or access healthcare in the other, realising that lifestyle can be difficult for people with disabilities (PWD). Limited cross-border services currently available to PWD not only suffer from poor awareness and adoption but also fail to meet PWD’s manifold individual needs. Thus facing restricted individual social space, especially in rural areas, the region’s PWD experience various constraints to self-determined lives, which the COVID-19 pandemic’s isolation and heightened border control have only aggravated. Against that background, we sought to identify factors that have enabled or constrained PWD’s individual agency in the Bavaria–Tyrol border region both before and during the pandemic. Methods: Beginning in April 2020, we conducted 34 semi-structured interviews with PWD, their relatives and employers and various institutional, political and administrative personnel regarding the use of cross-border education, housing, leisure and occupational services during the COVID-19 pandemic in Bavaria, Germany, and Tyrol, Austria. In qualitative content analysis, we summarised the most pressing results into eight abstracts that we later compiled into a qualitative online survey completed by 51 of 229 interviewees and other participants (22.27%). Results: Pandemic-associated developments and policies have been external shocks to an already fragile (cross-border) support system for PWD. Added to pre-pandemic obstacles including a lack of information, consensus and options regarding cross-border activities, new deficits in mobility, housing and funding for support along with prejudices and the effects of digitalisation have further intensified challenges for PWD.